Premchand: A Prolific Novelist - Surendra Kumar , Gupta (International Journal of Psychosocial Rehabilitation, 2015)
India has been the cradle of Ganga-Yamuni culture. The culture in which humanity dominates the minds of the people. There is no room for violence, and humanity creates peace. All religions and cultures are respected here and thoughts are accommodated. Premchand was a precious jewel of this culture. The novelist and short-story writer Premchand is considered to be the first major novelist in Hindi and Urdu of the twentieth century. Born on 31 July 1880 in Lamhi, a village in Varanasi, Premchand’s actual name was Dhanpat Rai Shrivastava. He belonged to the Kayastha family who used to hold important positions at that time, especially during the Mughal period. His grandfather Guru Sahai himself was a Patwari (land record keeper) and uncle Mahabir a big landowner. His father Ajaib Lal was a post office clerk. But beyond the identity of the ancestors, Premchand made his unique identity - an identity of an author who preferred Hindustani language over Hindi and Urdu as medium of expression. It was his extraordinary style of writing in composite culture that made him the samraat (emperor) of Hindi novels. Though we saw some names in the world of novel even much before Premchand such as Pariksha Guru by Lala Shrinivas Das(1882), Chatidrakanta Santati by Devaki Nandan Khatri (1890), Upanyas, a journal launched by Kishorilal Goswami (1998) in which his sixty five novels were published. But all these were like fables, away from the social issues and reality. It was Premchand’s pen which made social reality its subject matter. He not only provided literature to the society but picked up the characters from the society itself and explained them in their work. His distinctive style of writing made him stand a part. He did not adopt Sanskrit-influenced Hindi or Persianised Urdu, but adopted the Hindi-Urdu confluence as his companion and was proud of it. Today we consider it to be the common heritage of Hindi and Urdu. He said, Just as the language of English people is English, Japanese of Japan, Iranian of Iran, Chinese of China, it is not only appropriate to call the national language of India -Indian but necessary to do the same with the same weight. His prolific style of writing coupled with the reflection of problems of ordinary people in society reached out to the general public. Premchand once said, We will have to raise the standard of our literature, so that it can serve the society more usefully…our literature will discuss and assess every aspect of life and we will no longer be satisfied with eating the leftovers of other languages and literatures. We will ourselves increase the capital of our literature. The composite culture started in his early days of childhood when he started learning Persian and Urdu in a Madrasa in Lalpur near Lamhi. He studied Persian for around eight years from a Maulvi whose teaching had a profound effect on his mind as a result his writings became a model of Hindu-Muslim solidarity. He found Hindi also a useful communication language as there was a major part of the society who used Hindi.